Optimization for minimum manufacturing costs of tower cranes based on the plant growth simulation algorithm. Issue 2 (1st February 2023) - Li, Yinqi; Wang, Long; Liu, Feng; Li, Lijuan; Chen, Yulong
Abstract : Tower cranes are the most widely used lifting equipment in the construction industry. Studies on structural optimization have generally been conducted to achieve the lightest weight. Although the lighter structural weight generally brings lower manufacturing costs, the objective of minimum structural manufacturing costs for tower cranes has not been investigated extensively. In this study, a full parametric model of a tower crane was established based on the data provided by an enterprise to minimize manufacturing costs. The maximum error was within 9.5% of the actual costs for the enterprise. The main procedure was developed using the plant growth simulation algorithm (PGSA) to solve the numerical model, which requires the subprocedures of finite element analyses and manufacturing cost computations. The results showed that the optimal plan decreased the manufacturing cost of the tower crane by 15.94%, which was 2209.5 yuan lower than that of the lightest weight design.